1301 Early MRI in the Diagnosis of Suspected Scaphoid Fractures – An Audit of a Redesigned Diagnostic Pathway. (12th October 2021) - Cullen, J; Donovan, R; Vipulendran, K; Lostis, E; Blewitt, N; Kelly, M; Bott, A
Abstract: Introduction: MRI is the gold standard for investigation of suspected scaphoid fractures, which can be missed on initial x-rays. This full cycle audit reports the impact of our new patient pathway, which changes repeat x-rays at 2 weeks to urgent limited sequence scaphoid MRI for those with normal initial x-rays, but clinical suspicion of fracture at initial clinic visit. Method: A second cycle audited MRI requests for suspected scaphoid fractures at Southmead hospital following implementation of the new pathway in October 2020. We collected wait times from request to scan, and radiologist reports. Results were compared to our first cycle, 6-month time period. Results: he results for 24 limited sequence MRIs via our new pathway were compared to 134 full wrist MRIs of the first cycle. Two scans (9.1%) were positive for scaphoid fracture versus 12% in the first cycle. 19 scans (86%) identified alternate pathology including sprain (6), bone bruise (5), non-scaphoid fractures (4) and degenerative change (3). 1 scan (4.5%) was reported as normal. 73% of MRIs were performed within 14 days, compared to 63% in previous cohort. Conclusions: Our new pathway using limited sequence MRI identified similar rates of scaphoid fractures. Reduced time to MRI was observed compared to the previous cohort due to shorter scan durations and resulted in earlier diagnosis and fewer outpatient follow-up appointments. Our new pathway has benefits to patient experience and also reduces footfall in hospital, during a time of global Covid-19 pandemic, with no increase in costs.